Case Report: A rare case of prune belly syndrome with intraperitoneal cryptorchidism - Ji, Weiwei; Xue, Huiling; Gu, Ying; Wan, Yanmin; Lu, Liangsheng; Fan, Yong (Frontiers in Pediatrics, 2025)
Prune belly syndrome (PBS), a rare congenital disorder characterized by the absence of abdominal wall musculature and abnormalities in the genitourinary tract, is primarily linked to the urethral obstruction during fetal development. Given the overall rarity of the PBS and its multisystem involvement, there is currently no consensus on the optimal management strategy for PBS patients. This case report elaborated the comprehensive therapeutic outcomes of a patient with PBS, who had previously undergone several surgeries, including vesicoscopic cross-trigonal ureteral reimplantation, and first-stage Fowler-Stephens orchiopexy (FSO) for right cryptorchidism. At the age of seven, the patient underwent one-stage FSO combined with microvascular anastomosis for the left intra-abdominal testis. With appropriate perioperative management, the left testis was successfully survived. Herein, we presented an illustrative case to serve as a treatment reference for PBS patients.